Environmental drivers on leaf phenology of ironstone outcrops species under seasonal climate - GARCIA, LETÍCIA C.; BARROS, FERNANDA V.; LEMOS-FILHO, JOSÉ P. (Anais da Academia Brasileira de Ciências, 2017)
Banded iron formations (BIF) have a particular vegetation type and provide a good model system for testing theories related to leaf phenology, due to unique stressful environmental conditions. As a consequence of the stressful conditions of BIF environment, we hypothesize that most species would retain at least some significant canopy cover, even at the end of the dry season, independently of growth form - trees, shrubs, and sub-shrubs. Considering the strong seasonality, we also hypothesize that photoperiod and rainfall act as triggers for leaf fall and leaf flushing in these environments. The majority of the fifteen studied species had a semi-deciduous behavior and shed their leaves mainly during the dry season, with a recovery at the end of this season. In general, leaf flushing increased around the spring equinox (end of the dry season and start of the rainy season). A trade-off between leaf loss and leaf maintenance is expected in a community in which most plants are naturally selected to be semi-deciduous. Our results suggest photoperiod as a dominant factor in predicting leaf phenology.